Surface morphology, structural and electrical properties of electrodeposited Fe85Ni15/ITO films - Nemla, Fatima; Cherrad, Djellal; Aida, M.S.; Layadi, A. (Science des matériaux (Laboratoire LARHYSS), 2015)
Series of Fe85Ni15 films have been grown on tin-doped indium oxide (ITO)-coated glass substrates by the electrodeposition technique. The samples were made using different chemical potentials and deposition times, t. The structural properties and the surface morphology have been studied by the X-ray diffraction (XRD), scanning electron microscope, equipped with high power optics thermal field Emission (SEM–TFE) and a surface profilometry. The electrical properties were inferred from Hall effect measurements. The texture, lattice parameter, grain size, surface roughness, sheet resistance and electrical resistivity have been investigated. As the deposition time t increases, a change in texture from <110> to <211> is observed. This change strongly affects grain size, surface roughness behaviors and the electrical properties. These various experimental results will be discussed and correlated. Keywords: A. Thin films, A. NiFe alloy, C. X-ray diffraction, D. electrical properties. PACS: 73.61.At, 81.20.-n, 75.50.Bb, 07.85.Jy, 81.10.-h